Weathering in the Ganga Alluvial Plain: Geochemical signatures linking of the Himalayan source and the Bay of Bengal sink - Singh, Indra Bir; Singh, Sandeep; Singh, Munendra (Himalayan Journal of Sciences, 2008)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <![endif]–> DOI = 10.3126/hjs.v5i7.1327 Himalayan Journal of Sciences Vol.5(7) (Special Issue) 2008 p.146